Inverted Femoral Head Graft versus Standard Core Decompression in Nontraumatic Hip Osteonecrosis at Minimum 3 Years Follow-up. Issue 1 (January 2017) - Sallam, Asser A.; Imam, Mohamed A.; Salama, Khaled S.; Mohamed, Osman A.
Purpose: Numerous salvage surgeries were popularised to halt the progression of hip osteonecrosis (ON). We aimed to compare the clinico-radiological outcomes of inverted femoral head graft (IFHG) versus standard core decompression (SCD) in treatment of nontraumatic hip ON at pre-arthritic stage. Methods: A case review was performed at a minimum 3 years follow-up of 61 patients (71 hips; mean age 32.96 (19-50) years; mean follow-up 7.86 (3-14) years; mean body mass index 28.58 (19-46); 32 males, 29 females) suffering nontraumatic hip ON at pre-arthritic stage. 38 hips underwent SCD and 33 IFHG. The outcome was assessed by changes in modified Harris Hip Score (MHHS), need for revision surgery and progression of modified Ficat-Arlet staging. Data were analysed including logistic regression and Kaplan-Meier survivorship analysis. Results: 13/34 (38.2%) hips in SCD group were revised at 4.61 ± 2.61 years, while 7/33 (21.2%) in IFHG group at 8.43 ± 4.32 years (p = 0.023). MHHS was significantly higher in IFHG group at 1 and 3 years as well as at last follow-up (p = 0.014, 0.001 and 0.023 respectively). Clinical and radiological significant differences were found in survivorship analysis between both groups, in favor of IFHG. A higher clinical failure was noted among obese patients. Conclusions: An IFHG technique offers a better alternative regarding postoperative clinico-radiological outcomes in nontraumatic hip ON at the pre-arthritic stage. A cautious prognosis is recommended in obese patients.